Security interests under the UNIDROIT Convention on International Interests in Mobile Equipment 2001 - Saidova, Sanam (2012)
This work examines security interests under the Cape Town Convention on International Interests in Mobile Equipment. The main purpose of the Convention is to provide a uniform legal regime for the creation, registration and protection of a creditor’s interests held in high value types of mobile equipment, such as aircraft, railway and space objects. The Convention provides for the creation of an autonomous international interest in these types of equipment and establishes an electronic International Registry for recordation of interests in aircraft objects. The international interests are supported by an elaborate system of remedies exercisable in the case of the debtor’s default or insolvency. These features of the Convention are aimed at promoting predictability and transparency in the financing of mobile equipment which should reduce the risks and costs of borrowing to the benefit of all stake holders. The work examines such issues as the problems of the definition and creation of security interests as well as the possibility of the creation of a floating security under the Convention. It also explores the aims and assesses the effectiveness of the registration system established under the Convention. Next, the thesis examines the rules of the Convention on setting priorities between competing creditors. Finally, the work explored the remedies (and their effectiveness) available to the creditor. One of the aims of this work is to examine the provisions of the Convention and to test whether the legal regime created by it can operate successfully and help facilitate financing of high value equipment. In order to test the effectiveness of the Convention, its provisions will be evaluated in the context of various factual scenarios, which, considering the absence of cases under the Convention, were largely inspired by the experience of some major domestic jurisdictions, such as the UK and the US. This exercise may also shed some light on strengths and weaknesses of the Convention in comparison with these systems.